First evidence of the deletion in the pfhrp2 and pfhrp3 genes in Plasmodium falciparum from Equatorial Guinea - Pedro Berzosa; Vicenta González; Laura Taravillo; Alfredo Mayor; María Romay-Barja; Luz García; Policarpo Ncogo; Matilde Riloha; Agustín Benito (Malaria Journal, 2020)
Abstract Background The World Health Organization (WHO) recommends rapid diagnostic tests (RDTs) as a good alternative malaria-diagnosis method in remote parts of sub-Saharan Africa. The majority of commercial RDTs currently available detect the Plasmodium falciparum protein histidine-rich protein 2 (PfHRP2). There have also been recent reports of pfhrp2 gene deletions being found in parasites collected from several African countries. The WHO has concluded that lacking the pfhrp2 gene must be monitored in Africa. The purpose of the study was to analyse why the samples that were positive by PCR were negative by RDTs and, therefore, to determine whether there have been deletions in the pfhrp2 and/or pfhrp3 genes. Methods Malaria NM-PCR was carried out on all the samples collected in the field. A group of 128 samples was positive by PCR but negative by RDT; these samples were classified as RDT false-negatives. PCR was carried out for exon2 of pfhrp2 and pfhrp3 genes to detect the presence or absence of these two genes. Frequencies with 95% confidence intervals (CIs) were used for prevalence estimates. Associations were assessed by the Chi square test or Fisher´s exact test. The level of significance was set at p ≤ 0.05. Statistical analyses were performed using the software package SPSSv.15.0. Results After PCR, 81 samples were identified (4.7%, 95% CI 3.8–5.8) which had deletion in both genes, pfhrp2 and pfhrp3. Overall, however, 11 samples (0.6%, 95% CI 0.36–1.14) had deletion only in pfhrp2 but not in pfhrp3, and 15 (0.9%, 95% CI 0.6–1.5) presented with deletion only in pfhrp3 but not in pfhrp2. Considering the pfhrp2 gene separately, within the total of 1724 samples, 92 (5.3%, 95% CI 4.37–6.5) had evidence of deletion. Conclusion The present study provides the first evidence of deletion in the pfhrp2 and pfhrp3 genes in P. falciparum isolates from Equatorial Guinea. However, larger studies across different regions within the country and across different seasonal profiles are needed to determine the full extent ...